(3GddWGFa GdfhQjI aj GdefM GdOefghQjIs - (3GdOefghQj , CMeO Hf YHO GdefYe Hf jhSa Hf UjGe GdOefghQj, SQGL GdOjf,J (B1192 (3g` s
(3ChdgG (B:s
(3MekOG def MdGfG HMSf GdGJHGY s
(3hgh agQS HCSeGA heTGjN GdeDda GdPjf CNP Yfges
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B164 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B303s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B498 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B224 s
(3eUOQ GbJfGA GdCUd (B:s
(3ShgGL (B((3JGQjN (B232) s
Keywords: (3GdJGQjNs